Spin and magnetic moment of 23Mg. (31st May 2017) - Yordanov, D T; Bissell, M L; Blaum, K; Rydt, M De; Geppert, Ch; Krämer, J; Kreim, K; Kowalska, M; Krieger, A; Lievens, P; Neugart, R; Neyens, G; et al.
Abstract: A negative magnetic moment of 23 Mg has been determined by collinear laser spectroscopy at CERN-ISOLDE. The absolute value is in agreement with previous measurements by nuclear magnetic resonance while the sign points at high-seniority configurations. The result is consistent with shell-model predictions for nuclei with valence nucleons in the sd shell.